Successful isolation of schizochytrium - a new heterotrophic marine microalga containing high polyunsaturated fatty acid - dha from Phu Quoc district coasts - Hong, Dang Diem; Anh, Hoang Lan; Hoai Thu, Ngo Thi (Academia Journal of Biology, 2014)
Polyunsaturated fatty acids - PUFAs have known such as essential components of the cell membranes of various tissues and as precursors of the eicosanoids that are special importance in the brain and blood vessels, and are considered essential for pre - and post - natal brain and retinal development. In PUFAs w-3, docosahexaenoic acid (DHA) is absolutely necessary for normal development of the fetus and baby. DHA has some positive effects on human diseases such as hypertension, arthritis, arteriosclerosis, depression and thrombosis…. Therefore, DHA has contributed to many kind of worth product such as milk for pregnant woman and baby, drugs and functional food for human and animals. In this paper, for the first time, we succeeded in isolating of Schizochytrium sp. PQ6 and PQ7 - a new heterotrophic marine microalga, from Phu Quoc district coasts. The growth rate, dry weight, concentration of total lipid and the component of PUFAs in M1 media were analyzed in both strains. The DHA content of strains Schizochytrium sp. PQ6 and PQ7 are about 1.57 and 1.48 g/l, respectively. In comparison with other current marine microalgae in Vietnam, Schizochytrium sp. PQ6 and PQ7 have the highest concentration of PUFAs, especially content of DHA. That gives us new prospect for using these Schizochytrium as animal feed (e.g. for rotifer, krills, shrimp’s larvae, etc.) and functional food for human.